PENGARUH FAKTOR MAKROEKONOMI TERHADAP FINANCIAL DEEPENING DI INDONESIA - Sandi Mulyadi (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
The research background is the issue of research on the condition of financial deepening in Indonesia in 2013-2019 with the aim of describing the macroeconomic conditions of financial deepening in Indonesia for the period 2013-2019, using the variables foreign investment, trade openness, exchange rates, and inflation. The method used in this research is quantitative descriptive by analyzing secondary data which is processed using Eviews with the OLS method. The results of data processing using OLS show several findings, namely: foreign investment, exchange rates, and inflation variables have an effect on financial deepening and trade openness has no effect on financial deepening. Meanwhile, based on simultaneous testing, it shows that all macroeconomic variables have an effect on financial deepening in the 2013-2019 period. The implication of this research is that the government can maintain stable macroeconomic conditions and provide positive benefits for Indonesia's financial deepening.